Impatience and credit behavior: Evidence from a field experiment - Stephan Meier; Charles Sprenger (Federal Reserve Bank of Boston, 2007)
This paper tests whether heterogeneity of time preferences can explain individual credit behavior. In a field experiment targeting individuals from low-to-moderate income households, we measure individual time preferences through choice experiments, and then match these time preference measures to individual credit reports and annual tax returns. We find that, controlling for disposable income and other individual characteristics, individuals who are less patient have lower credit scores and higher default rates. Moreover, people with dynamically inconsistent (quasi-hyperbolic) preferences have higher active borrowing levels.
Keywords: D12; D14; D91; C93; 330; Time preferences; credit behavior; credit scores; delinquencies; field experiment; Verbraucherkredit; Konsumentenverhalten; Zeitpräferenz; Feldforschung; Massachusetts; USA